The Role of Social Media Marketing and Electronic Word of Mouth on Brand Image and Purchase Intention of SMEs Product - Mochammad Jasin (Journal of Information Systems and Management (JISMA), 2022)
This study aims to analyze the effect of social media marketing and electronic word of mouth on purchase intention through brand image. Methods This research is a quantitative research. Sampling The technique used is non-probability sampling by means of purposive samples. The sample used is 430 respondents, namely active social media users. Data collection The tool used is an online questionnaire distributed through social media. The data analysis technique used is structural equation modeling (SEM) analysis using the Smart PLS 3.0 program. Results of This study proves that Social Media Marketing has a positive and significant effect on Brand Image. Electronic word of mouth has a positive and significant influence on Brand Image. Social media Marketing has a positive and significant effect on Purchase Intent. Electronic Word of Mouth has a positive and significant impact on Purchase Intention. Brand Image has positive and significant effect on Purchase Intention. social media has a positive and significant effect on Purchase Intentions through Brand Image.